Origins of Catalyst Inhibition in the Manganese‐Catalysed Oxidation of Lignin Model Compounds with H2O2. Issue 13 (21st May 2019) - Barbieri, Alessia; Kasper, Johann B.; Mecozzi, Francesco; Lanzalunga, Osvaldo; Browne, Wesley R.
Abstract: The upgrading of complex bio‐renewable feedstock, such as lignocellulose, through depolymerisation benefits from the selective reactions at key functional groups. Applying homogeneous catalysts developed for selective organic oxidative transformations to complex feedstock such as lignin is challenged by the presence of interfering components. The selection of appropriate model compounds is essential in applying new catalytic systems and identifying such interferences. Here, it was shown by using as an example the oxidation of a model substrate containing a β‐O‐4 linkage with H2 O2 and an in situ‐prepared manganese‐based catalyst, capable of efficient oxidation of benzylic alcohols, that interference from compounds liberated during the reaction can prevent its application to lignocellulose depolymerisation. Abstract : Investigating inhibition : Upgrading lignocellulose by depolymerisation needs selective functional‐group transformation. A homogeneous catalyst based on Mn II and pyridine‐2‐carboxylic acid can oxidise model compounds bearing the β‐O‐4 linkage with H2 O2 selectively but is inhibited by catechol‐based compounds present in lignocellulose through chelation, preventing application to lignocellulose depolymerisation.